KEBERAGAMAAN ORANG JAWA DALAM PANDANGAN CLIFFORD GEERTZ DAN MARK R. WOODWARD: Javanese Diversity In The View Of Clifford Geertz And Mark R. Woodward - Shoni Rahmatullah Amrozi (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2021)
Artikel ini membahas perbedaan pandangan Clifford Geertz dan Mark R. Woodward tentang keberagamaan orang Jawa. Kedua pandangan ini menjadi rujukan bagi para intelektual yang mendalami kajian tentang agama (Islam) di masyarakat Jawa. Geertz mengkategorikan kelompok agama dalam masyarakat Jawa (Abangan, Santri, dan Priyayi) berdasarkan penelitiannya di Mojokuto (Pare, Kediri, Jawa Timur). Sementara itu, Mark R. Woodward meneliti keberagamaan orang Jawa di Yogyakarta. Woodward menganggap Yogyakarta sebagai pusat budaya masyarakat Jawa dan dianggap mampu mengkolaborasikan Islam dan budaya lokal. Artikel ini menyimpulkan bahwa Geertz menilai bahwa keberagamaan orang Jawa terkait dengan ketaatan dan ketidaktaatan. Sementara itu, Woodward melihat keberagamanan ini sebagai salah satu bentuk tafsir terhadap Islam oleh masyarakat Jawa.. This article examines the different views of Clifford Geertz and Mark R. Woodward about Javanese religiousness. Both of their studies, even today, have become references for intellectuals who study religion (Islam) in Javanese society. Geertz categorized the religious groups in Javanese culture (Abangan, Santri, and Priyayi). Geertz's (the 1950s) view have based on his research in Modjokuto (Pare, Kediri, East Java). Meanwhile, Mark R. Woodward researched Javanese religiousness in Yogyakarta (the 1980s). Woodward observed Yogyakarta as the cultural center of Javanese society. It is considered capable of collaborating between Islam and local culture. The article concludes that Geertz assessed that Javanese religiousness was related to religious obedience and disobedience. Meanwhile, Woodward sees this diversity as a type of interpretation of Islam by the Javanese community.